Advanced Business Law and the Legal Environment - Mayer, Don; Warner, Daniel; Siedel, George J.; Lieberman, Jethro K.; Martina, Alyssa Rose (Open textbook library., 2012)
Mayer, Warner, Siedel and Lieberman's Advanced Business Law and the Legal Environment is an up-to-date textbook with coverage of legal and regulatory issues that are more technical than the topics in the authors' Foundations of Business Law and the Legal Environment. Appropriate for students who have already taken an introductory Legal Environment or Business Law course, the text is organized to permit instructors to tailor the materials to their particular approach. The authors take special care to engage students by relating law to everyday events with which they are already familiar with their clear, concise and readable style. Advanced Business Law and the Legal Environment provides students with context and essential legal concepts relating to the Uniform Commercial Code and various aspects of property law. The text provides the vocabulary and legal savvy necessary for business people to talk in an educated way to their customers, employees, suppliers, and other stakeholders — and to their own lawyers.